Resting energy expenditure is not associated with disease activity in women with rheumatoid arthritis: cross-sectional study - Choe, Jung-Yoon (The Korean Association of Internal Medicine, 2014)
BACKGROUND/AIMS: Increased resting energy expenditure (REE) in rheumatoid arthritis (RA) patients is thought to be caused by hypermetabolism associated with production of proinflammatory cytokines. Our aim in the present study was to explore the possible association between REE and disease activity in females with RA. METHODS: A total of 499 female RA patients were recruited to this cross-sectional study assessing REE scores on disease activity indices (the routine assessment of patient index data 3 [RAPID3], the disease activity score 28, and the clinical/simplified disease activity index [CDAI/SDAI]) and the levels of RA-associated autoantibodies (rheumatoid factor and anticyclic citrullinated peptide [anti-CCP] antibodies). Age-matched healthy female controls (n = 131) were also enrolled. RESULTS: REE did not differ between RA patients (all patients, and those in remission or not) and controls, or between RA patients in remission or not (p > 0.05 for all comparisons). Increased REE in total RA patients was associated with younger age and a higher body mass index (BMI) (p < 0.001 and p < 0.001, respectively), but not with disease activity index scores on any of RAPID3, CDAI, or SDAI. BMI was the only clinical parameter exhibiting a significant relationship with REE quartiles (Q1 to Q4; p < 0.001); none of disease duration, functional status, or anti-CCP antibody titer in RA patients was significantly related to REE, based on analysis of covariance. CONCLUSIONS: We found no association between REE and disease activity in RA patients, implying that energy metabolism in RA patients might be independent of RA-associated systemic inflammation.